OF GODS AND MONSTERS: NATIONAL SECURITY AND CANADIAN REFUGEE POLICY - Aiken, Sharryn (Revue québécoise de droit international / Quebec Journal of International Law / Revista quebequense de derecho internacional, 2001)
The fiftieth anniversary year of the 1951 Convention affords an appropriate juncture to turn our gaze to the pledges Canada has made as a signatory state and the extent to which Canadian refugee policy has been “securitized” at the expense of vulnerable refugees and the very objectives the Convention was designed to address. Through the lens of the legal standards established by the Convention as well as complementary international norms and jurisprudence, this paper considers Canada's contemporary record on refugee issues with specific reference to the national security dimension of domestic policy. The author begins by tracing the evolution of refugee law and policy during the Cold War period, as well as parallel developments in the area of immigration security. The primary focus then turns to the anti-terrorism and security measures implemented by the federal government in 1992, together with proposals for reform under review in the Canadian Senate. The author concludes by locating the coordinates of an alternative approach to national security, one which incorporates the legal standards and normative values codified in the Refugee Convention. It is an approach that is premised on the overarching objective of bridging the chasm between “civilized self” and “barbaric other,” of enhancing human security for refugees and host population alike.